A new anisakid species parasitizing the imperial cormorant Phalacrocorax atriceps from the north Patagonian coast, Argentina - Garbin, Lucas; Diaz, Julia Inés; Cremonte, Florencia; Navone, Graciela Teresa (Journal of Parasitology)
The anisakid species Contracaecum chubutensis n. sp. was found parasitizing the imperial cormorant Phalacrocorax atriceps at 2 different localities, Bahía Bustamante (45°11'S, 66°30'W) and Puerto Madryn (42°47'S, 65°02'W) on the Patagonian coast. Morphometrical analysis and further studies of adult specimens of C. chubutensis n. sp. and fourth-stage larvae of Contracaecum sp. were done using light and scanning electron microscopy. The possession and disposition of 7 pairs of tail papillae differentiate this new species from C. osculatum, C. radiatum, C. plagiaticium, and C. mirounga. Double-sized spicules separate it from C. variegatum and C. pelagicum. Moreover, the paracloacal papillae disposition and tail shape differentiate this new species from C. travassosi. The presence of bifurcated interlabia separate it from C. ogmorhini and C. margolisi. Three well-marked lip notches, a sharp tail shape, and the of the transversal paracloacal papillae disposition distinguishes C. chubutensis n. sp. from C. magnipapillatum and C. septentrionale. The species here described can be differentiated from C. caballeroi by its bifurcated interlabia, longer spicules, and for possessing more precloacal papillae pairs. It can be separated from C. rudolphii by a thinner interlabia at the base, deeper lip notches, a sharper tail, the disposition of transversal paracloacal papillae, and greater distance between both papillae of the first subventral distal papillae pair. In addition, fourth-stage larvae recovered from the same host and localities were identified and described as Contracaecum sp. Prevalence of adult parasites was 66.7 %, mean intensity was 4.0, and mean abundance was 7.1. Fil: Garbin, Lucas. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina Fil: Diaz, Julia Inés. Consejo ...